APPLICATION OF POINT-CENTERED QUARTER METHOD FOR MEASUREMENT THE BEACH CRAB (Ocypode spp) DENSITY - Marisa, Hanifa (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2015)
Point Quarter Method is a plant community structure measurement procedure. The technique is base on measurement of distance of four plants or trees in every quarter that is made by four space in the cross line sampling field studies. In forest sampling, point centered quarter methods is considered as the efficient, reliable and accurate data, not only for mean distance and density, but for frequency and dominance of species. So it is important to try wether these method ould be applicated to animal, especially crab. These method was applicated for crab population in Padang Beach at December 22nd, 2014. Ten points quartered were made and the distance of every Ocypode sp crab burrow was counted by ruler. Mean distance of crabs burrow gained by divided of total number of quarter (20) with mean distance of every burrow to the point. Density per hectare is 10,000 m divided by quadratic of mean distance. Mean distance of burrow to points were counted and prediction of population per hectare could be found. In these case, mean distance was: 0.41 m and crab population is :59,488.34 individu per hectare. Compared to other species , eg Scylla serrata, its population is bigger, eventhough the condition of beach is polluted and wastedKeywords: point centered quarter method, Ocypode sp, density